Estimasi Daya Dukung Mass Balance terhadap Efluen Tambak di Desa Sebamban Baru Kabupaten Tanah Bumbu Provinsi Kalimantan Selatan - Fatmawati Fatmawati; K Soewardi; T. Kusumastanto; L. Adrianto (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
The purpose of this study was to estimate the carrying capacity of coastal waters ofthe pond effluent. The data required for analysis of mass balance models of carryingcapacity is based on the total ammonia-nitrogen (NH3-N) concentration in coastalwaters. Estimation of carrying capacity with the concept mass balance model usingthe formula Tchobanoglous (1990) and Predalumpaburt (1996) in Tookwinas (1998)which has been modified by including the formula Widigdo and Pariwono (2001). Carrying capacity of coastal waters of Sebamban Baru Village, Tanah BumbuRegency maximum pond area calculation may be developed for aquaculture area of 412,583 hectares, this shows that the concentration of ammonia released by thepond has not been an impact on the quality of coastal waters because the existingpond area is new opened an area of 368.542 ha has not exceeded the carryingcapacity of the mass balance.